Influence of nanoporosity on the nature of hydroxyapatite formed on bioactive calcium silicate model glass. Issue 4 (29th September 2018) - Thamma, Ukrit; Kowal, Tia; Falk, Matthias; Jain, Himanshu
Abstract: For hard tissue regeneration, the bioactivity of a material is measured by its ability to induce the formation of hydroxyapatite (HA) under physiological conditions. It depends on the dissolution behavior of the glass, which itself is determined by the composition and structure of glass. The enhanced HA growth on nanoporous than on nonporous glass has been attributed by some to greater specific surface area (SSA), but to nanopore size distribution by others. To decouple the influence of nanopore size and SSA on HA formation, we have successfully fabricated homogeneous 30CaO‐70SiO2 (30C70S) model bioactive glass monoliths with different nanopore sizes, yet similar SSA via a combination of sol–gel, solvent exchange, and sintering processes. After incubation in PBS, HA, and Type‐B carbonated HA (HA/B‐CHA) form on nanoporous monoliths. The XPS, FTIR, and SEM analyses provide the first unambiguous demonstration of the influence of nanopore size alone on the formation pathway, growth rate, and microstructure of HA/CHA. Due to pore‐size limited diffusion of PO4 3−, two HA/CHA formation pathways are observed: HA/CHA surface deposition and/or HA/CHA incorporation into nanopores. HA/CHA growth rate on the surface of a nanoporous glass monolith is dominated by the pore‐size limited transport of Ca 2+ ions dissolved from nanoporous glass substrates. Furthermore, with increasing nanopore size, HA/CHA microstructures evolve from needle‐like, plate‐like, to flower‐like appearance. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 886–899, 2019.